Very Large Atrial Septal Defect Device Closure: Feasibility and Safety - Datta, Goutam (The Indonesian Heart Association, 2021)
Objectives: There is limited data regarding feasibility and safety of very large ASD devices deployment. Percutaneous closure of very large atrial septal defect (ASD) is a valid alternative to surgical approach. But complications like erosion, cardiac perforation, atrioventricular block, pericardial effusion, infective endocarditis, or cardiac arrhythmias may occur following ASD device closure. Methods: Forty four patients with very large ostium secundum ASD were studied in a tertiary medical centre. Adult patients with defect size of 38 mm or more and device size of 40 mm or more were selected for device closure. Patients having suitable anatomy, significant left to right shunt(>1.5:1) ,right ventricular volume overload and without significant pulmonary arterial hypertension were chosen for device closure. Results : There were thirty six female patients and eight male patients in our study. Majority of our patients (twenty four) were in forty to fifty years age group. Device could be deployed successfully in forty two (95.5%). Twelve patients had device size of 46 mm (27%). Eight patients had 44 mm devices(18%). Forty two millimeter devices were used in sixteen patients (36%). Eight patients had device size of 40 mm(18%).Device embolization occurred in two patients. There were two cases of pericardial effusion and pericardiocentesis was needed in one patients. Transient complete heart block was seen in one patient. Four patients had suffered from transient and self terminating atrial arrhythmias. There was no mortality or erosion in our study. Conclusion: Percutaneous closure of very large ASD is feasible and associated with low complication rate